2021
DOI: 10.1364/ol.418570
|View full text |Cite
|
Sign up to set email alerts
|

Coupled cavity-waveguide based on topological corner state and edge state

Abstract: Topological corner state (TCS) and topological edge state (TES) have provided new approaches to control the propagation of light. The construction of topological coupled cavity-waveguide system (TCCWS) based on TCS and TES is worth looking forward to, due to its research prospects in realizing high-performance micro-nano integrated photonic devices. In this Letter, TCCWS is proposed in two-dimensional (2D) photonic crystal (PC), which possesses strong optical localization, high quality factor and excellent rob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…[ 32 ] The possibility of the existence of TES at the interface along the xfalse(yfalse)$x( y )$ direction arise from two PCs with a Zak phase difference along the yfalse(xfalse)$y( x )$ direction. [ 37 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 32 ] The possibility of the existence of TES at the interface along the xfalse(yfalse)$x( y )$ direction arise from two PCs with a Zak phase difference along the yfalse(xfalse)$y( x )$ direction. [ 37 ]…”
Section: Resultsmentioning
confidence: 99%
“…[32] The possibility of the existence of TES at the interface along the x(y) direction arise from two PCs with a Zak phase difference along the y(x) direction. [37] When two PCs with different topological properties are placed in contact, their combined structure will lead to TES at a combination interface (See Section SII, Supporting Information). The photonic crystal waveguide (PCW) based on the TES (that can be named topological-PCW) supports a topologically protected unidirectional propagation edge state without backscattering.…”
Section: Resultsmentioning
confidence: 99%
“…When we increased the operating frequency of the waveguide-resonator device to coincide with the corner states at 5.93 GHz, surprisingly, it was observed that despite the fact that this frequency also cut through the E 2 edge dispersion, the incoming wave from the edge port only excited the corner states in the ring resonator (see Figure 3 c). This is due to the large quality factor known for the topological corner states [ 51 , 52 ]. More interestingly, Figure 3 c shows that the anti-chiral E 4 edge states can go around the lower-right sharp corner to illuminate the upper corner of the triangular ring, indicating their topological robustness.…”
Section: Reconfigurable Light Imagingmentioning
confidence: 99%
“…Therefore, the optimization of Q is essential for further investigation of corner state, which still lacks except for the method reported in our previous works by changing the gap between two PhCs [55,56]. Additionally, although the robustness of the corner state against disorders in the topological nanocavity has been discussed in previous works [56,57,59], they are mainly the theoretical discussions, which just focus on one kind of specific defect or perturbation. A systematic study on the robustness with the experimental demonstration in particular has been rarely undertaken.…”
Section: Introductionmentioning
confidence: 99%